Optimalisasi Digital Marketing melalui Aplikasi Digital : Usaha UMKM Olahan Laut dan Pariwisata Kampung Nelayan Desa Salira - Ayu Nuryani; Munawaroh Munawaroh (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The purpose of this activity is to develop digital marketing skills through training on the use of digital applications Canva and Capcut to promote Micro, Small, and Medium Enterprises (MSMEs) in fish processing and tourism in the Fisherman Village located in Salira Village, Serang Regency. This activity aims for MSME entrepreneurs to enhance their skills in taking photos and videos, as well as processing these images and videos into more engaging, innovative, informative, and professional content.The method used in this activity involves training on the use of the Canva and Capcut applications with the theme "Application of CANVA and CAPCUT in Digital Marketing." The research results indicate a positive and significant improvement in marketing content compared to previous efforts. However, there are still challenges to address, such as the inadequate facilitation of supporting tools for content creation, which must be improved for the content produced to continue evolving for display on various digital marketing platforms.